Pengaruh Motivasi Dan Kontrak Psikologis Terhadap Kepuasan Kerja Serta Implikasinya Terhadap Kinerja Pegawai Politeknik Bumi Akpelni - Tini Utami; Suprihono Setyawan; Evyana Diah Kusumawati (Sekolah Tinggi Maritim Yogyakarta, 2021)
The perpose of this study was to determine the effect of motivation and psychological contracts on job satisfaction and its implications for employee performance at the Bumi Akpelni Polytechnic Semarang. This study is a quantitative descriptive study with a sample of 68 employees. The dependent variable in this study is job satisfaction and performance, while the independent variables are motivation and psychological contract. In this study using the method of purpose sampling as a sampling technique. The results of the study explain that the psychological contract variable has a t-count calculation (0.538) with a significance (0.000 <0.05) so it can be concluded that the psychological contract variable has a positive and significant effect, while the motivation variable has a result with a path calculation of (0.028). it means that the motivation variable is also said to have a positive effect through job satisfaction. It is explained in the first equation that the adjusted R2 square is 0.057 meaning 5.7% of the job satisfaction variable can be explained by the variation of the two independent variables, namely work motivation and psychological contract, while 94.3% is explained by other reasons outside this research model. in the second equation it is stated that the adjusted R2 square is 0.265, meaning that 26.5% of the performance variable can be explained by the psychological contract variable, while the remaining 73.5% is explained by other reasons outside this study.